Experimental study on ammonolysis process of copper(II) nitrate and copper oxide-copper nitride transformations - Szczęsny, Robert; Bogdańska, Katarzyna; Wiśniewski, Marek (Bulletin of the Polish Academy of Sciences Technical Sciences, 2026)
There has been renewed interest in copper nitride (Cu3N). New chemical methods have been developed to synthesize this compound in the last ten years. Although these approaches are based on the precipitation reaction exploiting different nitriding agents, an interesting issue is still the applicability of the gas (NH3) – solid ammonolysis process towards various precursors and the analysis of the course of this reaction. The nitridation processes of the copper(II) nitrate and the subsequent formation of copper oxide-copper nitride were analyzed in this study. The mentioned phase transformations were monitored in situ by infrared spectroscopy. Moreover, X-ray powder diffraction (XRD) and scanning electron microscopy (SEM) were employed for morphology and phase composition analysis. The results indicate that Cu(NO3)2 can serve as an effective direct Cu3N precursor. This ammonolysis reaction proceeded through the formation of copper oxides. Additionally, ammonolysis-oxidation tests between CuO and Cu3N indicate the full reversibility of these processes.